Effects of agroforestry and climate on cocoa yield, pests and diseases - Asitoakor, B.K. (University of Ghana, 2021)
Cocoa (Theobroma cacao) originates from the Amazon basin in South America. The crop is cultivated across many tropical regions, with the largest production from West Africa, where Ghana and Cote d’Ivoire contribute 70% of global production. Two major systems dominate cocoa production; a full-sun monocropping system where the cocoa crop is grown without shade trees, and an agroforestry system where cocoa is grown with deliberately planted or retained forest/fruit trees. Aside soil fertility and genotype influences on cocoa production, pests, diseases, and climatic conditions are major. Decades of chemical applications to control cocoa pests and diseases have undermined environmental integrity and increased production costs. The situation is likely to worsen under current and future climate change scenarios and negatively impact agricultural productivity. Choosing the right shade trees for agroforestry adoption is one identified strategy with carbon sequestration potential and the ability to minimize the influence of increased temperatures and reduced rainfall. Though cocoa under shade trees has many advantages, it is unclear if shade tree species differ in effects on soil fertility, yields, and pests and diseases infestation. Previous studies have reported farmers’ perceptions and willingness to adopt certain tree species in cocoa-agroforestry. However, there is little or no explicit scientific knowledge on the influence of specific shade tree species on cocoa productivity. This study evaluated the effects of different agroforestry shade tree species on soil fertility and cocoa yield. It also determined the impacts of agroforestry on mirids and black pod disease infestations in cocoa systems. The study further assessed the effects of agroforestry and climate variability on cocoa yield across a climate gradient in Ghana. Using 74 plots from 10 cocoa farms in the Western Region of Ghana, soil fertility and yield as influenced by eight (8) commonly retained forest shade tree species against unshaded control plots were examined during the 2018/2019 and 2019/2020 crop seasons. Soil samples from 0 - 30cm depth were taken at the beginning and the end of the study from each plot and tested for acidity (pH), concentrations of nitrogen (N), carbon (C), available phosphorus (P), magnesium ion (Mg2+), calcium ions (Ca2+) and sodium (Na+) using standard methods. The yield was measured as the total number of matured cocoa pods counted per hectare at harvest and the total dry weight of extracted cocoa beans in kilogram per hectare during two main crop and two light crop periods. Apart from available P, which was lower under shade trees than in control plots, the remaining soil properties tested were not significantly different. Through linear mixed effect models, the yield was significantly higher in shaded plots than in unshaded control plots. There were no significant differences in yield between the shade tree species. Yield in Terminalia superba, Khaya ivorensis and Cedrela odorata plots were 150 kg ha-1yr-1 higher than the yield in the unshaded control plots (303 kg ha-1yr-1). The population of mirid and the number of cocoa pods damaged by mirid and black pod disease infestations were counted monthly for the two years. On-farm temperature, rainfall, and relative humidity were measured using standard methods. Logistic regression with a nested-effects model was used to determine the variability in shade tree species influence on the mirid population. Linear mixed-effect models were used to assess the effects of shade tree species on the damaged pods. Mirid populations varied between species and over time, with no consistent high and low periods. Triplochiton scleroxylon and Alstonia boonei plots recorded the highest and lowest mirid occurrences compared with unshaded control plots. Pod damages due to mirid infestation varied with season and shade tree species, while pod damages from black pod disease infestation did not vary significantly with shade tree species. The fluctuations in monthly temperature, rainfall, and relative humidity corresponded with mirid populations and the number of pod damages from mirid and black pod disease infestations. The choice of shade tree species for adoption in cocoa-agroforestry systems is critical as they affect soil available P and yield. Also, the right selection of shade tree species could be a strategic tool in managing mirid and black pod disease infestation in cocoa agroforestry systems. In a 4-year (2016 – 2020) experiment, two aspects of cocoa productions; cocoa health and productivity, along a gradient of high rainfall/low temperature in the south to low rainfall/high temperature in the north of Ghana’s cocoa belt were assessed. Twenty-three (23) cocoa farms cultivated on previous forest lands along the gradient were used, with a systematic selection of 460 cocoa trees (20 per farm) from the south (N = 160), middle (N = 180), and north (N = 120) of the cocoa belts. The selected trees varied in stem diameter but were similar in distance to the nearest shade trees. Each cocoa tree was inspected and ranked monthly for tree vigour, canopy health, flower intensity, and the number of damaged pods due to mirids, cocoa shield bugs, and black pod disease infestations. The number of healthy young, matured and harvested cocoa pods, and the dry weight of cocoa beans were evaluated as parameters for productivity. Temperature, rainfall, and relative humidity for each region were monitored and influenced cocoa health and productivity differently. Variations were observed in flower intensity and canopy health along the gradient through ordinal logistic regression analysis. Linear mixed effect model analysis of the productivity indicators showed differences at p > 0.05. Cocoa outputs were highest in the south at annual 0.84 ± 0.14kg dry beans per cocoa tree, against 0.77 ± 0.04kg dry beans and 0.60 ± 0.04kg dry beans per cocoa tree in the middle and north, respectively. Insect pest infestation was highest in the north where temperature was highest with the least rainfall at 2.8 ± 0.01 infested pods per cocoa tree. Black pod disease infestation was similar in the south and middle at 0.5 pods per cocoa tree compared to 0.3 pods per cocoa tree in the north. Rainfall and relative humidity offset the effects of temperature and agroforestry in the cocoa systems. Cocoa cultivation in forest regions with higher rainfall and shade trees is likely to produce healthier and more productive cocoa trees. Further studies are needed to guide cocoa production and the inclusion of shade trees as components of cocoa-agroforestry. This is important considering current and future climate change scenarios in tropical regions and the need for cocoa yield sustainability.